2018
DOI: 10.1029/2018gl079533
|View full text |Cite
|
Sign up to set email alerts
|

Combined Scattering of Outer Radiation Belt Electrons by Simultaneously Occurring Chorus, Exohiss, and Magnetosonic Waves

Abstract: We report a typical event that fast magnetosonic (MS) waves, exohiss, and two‐band chorus waves occurred simultaneously on the dayside observed by Van Allen Probes on 25 December 2013. By combining calculations of electron diffusion coefficients and 2‐D Fokker‐Planck diffusion simulations, we quantitatively analyze the combined scattering effect of multiple waves to demonstrate that the net impact of combined scattering does not simply depend on the wave intensity dominance of various plasma waves. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…In contrast, Maldonado et al (2016) suggested that the formation of this featured distribution should be attributed to the bounce resonance by MS waves. In addition, the generation of the butterfly distribution owing to the competition between outer zone electron scattering by plasmaspheric hiss and MS waves has also been carefully studied (e.g., Hua et al, 2018Hua et al, , 2019Ni et al, 2017).…”
Section: Research Lettermentioning
confidence: 99%
“…In contrast, Maldonado et al (2016) suggested that the formation of this featured distribution should be attributed to the bounce resonance by MS waves. In addition, the generation of the butterfly distribution owing to the competition between outer zone electron scattering by plasmaspheric hiss and MS waves has also been carefully studied (e.g., Hua et al, 2018Hua et al, , 2019Ni et al, 2017).…”
Section: Research Lettermentioning
confidence: 99%
“…Radiation belt electrons can be affected by various magnetospheric wave modes, including whistler mode chorus, plasmaspheric hiss, magnetosonic waves, electromagnetic ion cyclotron waves, and electrostatic electron cyclotron harmonic waves, via wave-particle interaction processes (e.g., Ni et al, 2016;Shprits et al, 2008;Summers et al, 2007;Thorne, 2010), and ultralow frequency wave-driven diffusion (e.g., Su, Zhu, Xiao, Zong, et al, 2015). Among these waves, hiss is typically regarded as a structureless, broadband whistler mode emission naturally occurring inside the plasmasphere (e.g., Meredith et al, 2004;Thorne et al, 1973), high-density plasmaspheric plumes (e.g., Summers et al, 2008;Zhang et al, 2018), and lowdensity plasmatrough (Hua et al, 2018;Su et al, 2018a;Zhu et al, 2015). A few recent studies reported hiss emissions with short-time (tens of milliseconds) rising and falling tones (Summers et al, 2014), long-lasting (~1 s) rising tones, and large amplitude (up to 1.5 nT) hiss waveforms in the plasmaspheric plumes (Su et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The drift-collision-source model developed in this study only included PA diffusion from atmospheric collisions without considering the effect of wave-particle interactions. At L > 1.3, PA diffusion can also result from plasmas waves including plasmaspheric hiss (e.g., Cao et al, 2017;Hua et al, 2018Hua et al, , 2019Ni et al, 2013Ni et al, , 2014Xiang et al, 2016Xiang et al, , 2018Zhao et al, 2019), lightning-generated whistler mode waves (e.g., Meredith et al, 2009), and man-made very low frequency waves (Ma et al, 2017). It will be important to include the effect of various magnetospheric waves (e.g., Ni et al, 2017) in the drift-collision-source model to investigate their relative contributions to electron loss in the inner belt at larger L and the slot region, which we leave for future study.…”
Section: 1029/2019ja027678mentioning
confidence: 99%